2022
DOI: 10.3390/ph16010042
|View full text |Cite
|
Sign up to set email alerts
|

The Core-Targeted RRM2 Gene of Berberine Hydrochloride Promotes Breast Cancer Cell Migration and Invasion via the Epithelial–Mesenchymal Transition

Abstract: Berberine hydrochloride (BBR) could inhibit the proliferation, migration, and invasion of various cancer cells. As the only enzyme for the de novo synthesis of ribonucleotides, RRM2 is closely related to the development of tumorigenesis. However, not much is currently known about the functional roles of RRM2 in breast cancer (BRCA), and whether BBR regulates the migration and invasion of BRCA cells by regulating the expression of RRM2 remains to be determined. We study the effects of BBR on BRCA cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Multiple studies have reported a direct link between the overexpression of RRM2 in breast cancers and increased cell proliferation and invasiveness, as well as drug and chemotherapy resistance [ 12 , 13 , 29 , 31 ]. Previously, we found that RRM2 is upregulated in ER− and drug-resistant breast cancer cells, rationalizing our hypothesis of targeting ribonucleotide reductase for ER+ as well as ER− breast cancer treatment [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have reported a direct link between the overexpression of RRM2 in breast cancers and increased cell proliferation and invasiveness, as well as drug and chemotherapy resistance [ 12 , 13 , 29 , 31 ]. Previously, we found that RRM2 is upregulated in ER− and drug-resistant breast cancer cells, rationalizing our hypothesis of targeting ribonucleotide reductase for ER+ as well as ER− breast cancer treatment [ 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, RRM2 could enhance melanoma grow and promote cellular senescence 51 . In breast cancer, RRM2 accelerated cell migration and invasion via regulating epithelial-mesenchymal transition (EMT) process 52 . In head and neck and lung cancers, knockdown of RRM2 caused cell apoptosis via accelerating the degradation of Bcl-2 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Berberine (BBR) is a natural isoquinoline alkaloid isolated from plants of the genus Berberis, with therapeutic effects on gastroenteritis, hyperlipidemia, coronary heart disease, and other diseases. Notably, BBR showed inhibition of tumor cell proliferation, migration, and invasion in a variety of tumors. , Studies have shown that BBR not only has the ability to selectively reduce the viability of HCC cells without affecting normal hepatocytes but also effectively induces cell cycle arrest in the G1/S phase . AMP-activated protein kinase (AMPK), a metabolism-sensitive protein kinase, is involved in the regulation of cell growth, metabolism, apoptosis, autophagy, proliferation, and other physiological processes. AMPK has a strong pro-apoptotic potential under activated conditions, and BBR induces selective apoptosis in HCC cells by inhibiting the expression of the antiapoptotic factor BCL-2 and through an AMPK-mediated mitochondrial/caspase pathway. , Similarly, AKT is a serine/threonine kinase that plays a major role in the PI3K/AKT signaling pathway and is involved in regulating the cell cycle, autophagy, and apoptotic processes. , Clinical findings have shown that higher levels of phosphorylated (p)-AKT in tumors are one of the major contributors to the increase in tumor drug resistance. , BBR can also inhibit tumor progression and overcome tumor drug resistance through PI3K/AKT. , BBR is a potential natural anticancer drug due to its multiple anticancer targets and low biological toxicity.…”
Section: Introductionmentioning
confidence: 99%